2015
DOI: 10.3390/nu7053094
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and Its Supplementation in Cardiovascular Disease—What do We Know?

Abstract: The trace element selenium is of high importance for many of the body’s regulatory and metabolic functions. Balanced selenium levels are essential, whereas dysregulation can cause harm. A rapidly increasing number of studies characterizes the wide range of selenium dependent functions in the human body and elucidates the complex and multiple physiological and pathophysiological interactions of selenium and selenoproteins. For the majority of selenium dependent enzymes, several biological functions have already… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
181
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(209 citation statements)
references
References 126 publications
3
181
0
9
Order By: Relevance
“…The present study demonstrated that treatment with EPO reduced FBG, ameliorated glucose tolerance and insulin sensitivity, and lowered glyconeogenesis in experimental diabetic rats, which was in agreement with the previous studies. A previous randomized placebo controlled trial (18) demonstrated that insulin sensitivity is not improved following treatment with EPO in healthy humans. This may be due to exogenous EPO normalizing the low EPO levels in these patients.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The present study demonstrated that treatment with EPO reduced FBG, ameliorated glucose tolerance and insulin sensitivity, and lowered glyconeogenesis in experimental diabetic rats, which was in agreement with the previous studies. A previous randomized placebo controlled trial (18) demonstrated that insulin sensitivity is not improved following treatment with EPO in healthy humans. This may be due to exogenous EPO normalizing the low EPO levels in these patients.…”
Section: Discussionmentioning
confidence: 97%
“…Numerous clinical assays have demonstrated significantly lower plasma and serum concentrations of selenium in patients with cardiovascular diseases, compared with those measured in healthy individuals (18). Selenium is a trace element, which exerts certain insulin-like actions on the glucose homeostasis of diabetic rats.…”
Section: Epo Increases Blood Selenium In Diabetic Ratsmentioning
confidence: 99%
“…Selenium plays a role in many important physiological functions in human and animal health because it's a component of selenoproteins such as glutathione peroxidase, thioredoxin reductase, and thyroid hormone deiodinase families [2]. These Se dependent enzymes play a wide range of biological functions involving thyroid hormone metabolism, the body's antioxidant defense systems, the adaptive and acquired immune system and prevention of certain cancers [3]. In addition, selenoproteins such as glutathione peroxidase and thioredoxin reductase play an important role in maintaining bone homeostasis and protecting against bone loss [4].…”
Section: Introductionmentioning
confidence: 99%
“…3 Cardiovascular comorbidities are prevalent in individuals with obstructive sleep apnea (OSA). The most accepted hypothesis is that intermittent hypoxia leads to oxidative stress contributing to proatherogenic effects: lipid peroxidation, endothelial dysfunction, and systemic inflammation.…”
mentioning
confidence: 99%